Utilizing Metaverse Technology to Boost the Development of Culture and Tourism in Leizhou - Chen, Luying; Zhao, Daying (Transactions on Engineering and Computing Sciences, 2024)
This paper aims to explore the application of metaverse technology in the fields of culture and tourism in Leizhou, analyzing how it empowers new forms of cultural tourism through digital means and promotes the inheritance and development of Leizhou’s culture. The article first introduces the concept of metaverse technology and its application background in cultural tourism. It then elaborates on specific application cases of metaverse technology in Leizhou’s culture and tourism, including immersive cultural tourism experiences, digital preservation and inheritance of cultural heritage, and the application of virtual digital humans. Finally, the paper summarizes the advantages and challenges of metaverse technology in Leizhou’s culture and tourism and proposes corresponding countermeasures and suggestions.